(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2017)
Multistage education called forth the «Bachelor» segment at the education services market; it realizes the program of training the seekers of basic higher education. Higher educational establishments have been accumulating educational potential in this segment for a long time. The method for determination of the level of absolute and relative educational pragmatism concerning the bachelor-training educational and professional program in the activity of higher educational establishments in Poltava region has been created; it reveals the level of realization of the establishment educational potential. Absolute educational pragmatism demonstrates the educational establishment level of realization of the licensed amount for bachelor training in a particular specialty. Relative pragmatism demonstrates the establishment level of the use of the licensed amount in relation to other establishments training bachelors in the specialty.